Physiological and Behavioral Changes of Water Buffalo in Hot and Cold Systems: Review - Yáñez-Pizaña, Ariadna; Cruz-Cruz, uis Alberto de la; Tarazona-Morales, Ariel; Roldan-Santiago, Patricia; Ballesteros-Rodea, G.; Pineda-Reyes, Raym; Orozco-Gregorio, Héctor (Journal of Buffalo Science, 2020)
This review's objective is to provide information on the mechanisms that buffaloes express during the thermoregulation process. Generally, the water buffalo is associated with warm and tropical climates. In these systems, the combination of high temperature, relative humidity, and radiation cause different physiological and behavioral changes, particularly during the summer months. Wallowing behavior in water or mud promotes heat dissipation through physical mechanisms, such as conduction, convection, and radiation. Furthermore, the provision of natural or artificial shades contributes to thermoregulation and maintains homeostasis. In production systems in cold climates, the wallowing behavior is inhibited by the water temperature, so it is important to keep the animals protected in stables to avoid the cold winds and rapid drops in temperature, causing increased illness pneumonia and sometimes death. Finally, in cold conditions, the animals require an appropriate diet since the use of energy is distributed mainly for the production of heat. Thus, heat stress and cold stress generates relevant problems in health, welfare, and productivity in water buffaloes. A comprehensive assessment of the severity of the resulting problems associated with thermal stress and specialty in cold stress in water buffaloes is necessary so far, and there's very little information about it in this species.